Fabrication of Ti/SnO2-Sb/Ce-PbO2 Anode from Methanesulfonate Bath and Its Electrocatalytic Activity. Issue 13 (30th August 2019) - Xu, Pengfei; He, Xiaohong; Mao, Junwei; Tang, Yongming
Abstract : In this paper, Ti/SnO2 -Sb/Ce-PbO2 anode is electrodeposited from MSA bath, and the effect of Ce 3+ concentration in bath on the phase composition and morphology of lead dioxide electrode is elucidated. It is found that with the addition of 2 mM Ce 3+ ion to the bath the Ce-PbO2 anode exhibits highest stability in 0.5 M H2 SO4, and cerium exists as Ce (IV) in the PbO2 film. The electrocatalytic activity of lead dioxide anode for phenol removal is slightly enhanced by the inclusion of Ce. The significant improvement in electrocatalytic activity can be achieved by the addition of small amount of Bi 3+ ion to the bath containing Ce 3+ ion. In this study, electrocatalytic activities of various anodes follow the order: Ce, Bi-PbO2 > Ce-PbO2 > undoped PbO2 > Bi-PbO2 .